PENGARUH PSIKOEDUKASI PPENGARUH PSIKOEDUKASI TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN - Eti Surtiati; Yunani Sri Astuti (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Pregnancy is a natural thing that usually happens in women who is still productive. During the pregnancy, there are some changes to the mother, in both of physically as missing the periods, breast enlargement, shape changes of the uterus and psychologically as the feeling of anxiety in third trimester of pregnancy. Anxiety in pregnancy need to be handled seriously because it can turn into adverse outcomes to both of the mother and baby such as: increased the incidence of premature, low birthweight, post-natal depression, behavioral problems in the newborn and toddler period. It caused by the lack of information about signs and symptoms of labor to pregnant women that can be obtained through the psychoeducation. The purpose of research is to know the effect of psychoeducation to the level of anxiety of the third trimester pregnant women in dealing with labor in bogor hospital. Methods Design of the study is quasi-experimental pre - post with control group with psychoeducation intervention. The sampling is taken with purposive sampling with a sample of 82 third trimester pregnant women who will face labor, divided into the intervention and control groups. Results of bivariate analysis showed a mean value in the third trimester pregnant women before being given psycho-education (pre-test) = 23:15 and the mean value after being given psycho-education (posttest) = 12.91, with a p-value 0.047 at alpha p <0.05 then Ho is rejected, which means there is effect of psychoeducation to the level of anxiety of the third trimester pregnant women in dealing with labor in bogor hospital. The conclusion of this research is there is level of anxiety difference between the third trimester pregnant women in the intervention group before and after being given psycho-education. Recommendations that psycho-education may also be applied to the high risk third trimester pregnant women